2013 President's plenary international psycho‐oncology society: embracing the IPOS standards as a means of enhancing comprehensive cancer care. Issue 9 (21st June 2014) - Bultz, B.D.; Cummings, G.G.; Grassi, L.; Travado, L.; Hoekstra‐Weebers, J.; Watson, M.
Abstract Background The second President's Plenary at the 2013 International Psycho‐oncology Society's World Congress in Rotterdam, the Netherlands aimed to progress and, where needed, initiate changes to achieve comprehensive cancer care. Recent initiatives have been driven by the need to see psychosocial care as an integrated part of holistic multidisciplinary quality cancer care. The President's Plenary session covered the need for the following: An internationally agreed standard of quality cancer care, which includes psychosocial care for patients and their families and caregivers. An endorsement to assess distress as the 6th vital sign. Psycho‐oncology professionals to integrate into a federation promoting better national and international outcomes. Conclusion This overview highlights progress in terms of enhanced communication between and within different professionals groups supporting the implementation of a model of comprehensive patient care that is inclusive of psychosocial support and screening for distress. Tasks and challenges for the future are set out but the primary message is of the importance of collaboration in order to achieve recognition that psychosocial care is integrated into comprehensive cancer care; in this way, patient, family and carer needs can be more appropriately met. Copyright © 2014 John Wiley & Sons, Ltd.